Penal servitude: convicts and long-term imprisonment, 1853-1948 - Johnston, Helen (States, people, and the history of social change)
The Early Origins of a National Convict Prison System, 1779-1853 -- Building the Convict Prison Estate, 1853-78 -- Life in the Convict Prison I: Regime, Labour, and Education -- Life in the Convict Prison II: Progression and Resistance, Health and Diet -- The Prison Community: Gender, Sexuality, and Class -- Release: Theory, Policy, and Practice -- Recidivism, the Convict Prison Population, and the Gladstone Committee, 1880-1932 -- Conclusion.